Optimized output baluns for current mode class D power amplifiers - Kamper, Michael; Kondakov, Dmitrii; Fischer, Georg (8th German Microwave Conference, GeMiC 2014, 2014)
Baluns optimized for Current Mode Class D (CMCD) amplifiers are presented. CMCD amplifiers employ a differential output and therefore require a low loss balun to drive single ended loads. Furthermore, impedance termination at harmonic frequencies needs to be controlled to maintain high efficiency operation. In this work planar balun types are compared with respect to insertion loss and harmonic impedance behavior. Afterwards an exponentially tapered balun is designed, demonstrating a very low loss of 0.2 dB at 860 MHz.
CRIS-Team Scopus Importer:2019-10-22